2020
DOI: 10.5603/gp.a2020.0036
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and practice of ergonomics by gynecological laparoscopists in Turkey

Abstract: Objectives: Ergonomics in laparoscopy has been gaining increasing attention. The research literature on ergonomics is growing worldwide; however, there are no studies or data from Turkey. Our study provides information on the awareness and use of ergonomics in laparoscopic gynecology in Turkey. Material and methods:A questionnaire consisting of 25 questions was sent by email to 225 laparoscopists who are members of the Turkish Society of Gynecological Endoscopy. Results:In response, 45.7% of the questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…The estimated prevalence of musculoskeletal symptoms among gynecologic laparoscopic surgeons was 82% (95% CI, 70%–89%; I 2 , 92%), calculated from a pooled sample size of 1619 surgeons among the 12 studies included (Figure 4). 3,4,8–17 As studies varied in the type of prevalence reported, subgroup analyses were performed to estimate the lifetime, 12‐month, and point prevalence (Figure 5). The estimated lifetime prevalence was 90% (95% CI, 76%–96%; I 2 , 91%), based on data from six studies with a combined sample size of 626 3,4,10,12,13,15 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The estimated prevalence of musculoskeletal symptoms among gynecologic laparoscopic surgeons was 82% (95% CI, 70%–89%; I 2 , 92%), calculated from a pooled sample size of 1619 surgeons among the 12 studies included (Figure 4). 3,4,8–17 As studies varied in the type of prevalence reported, subgroup analyses were performed to estimate the lifetime, 12‐month, and point prevalence (Figure 5). The estimated lifetime prevalence was 90% (95% CI, 76%–96%; I 2 , 91%), based on data from six studies with a combined sample size of 626 3,4,10,12,13,15 .…”
Section: Resultsmentioning
confidence: 99%
“… 3,4,8–17 As studies varied in the type of prevalence reported, subgroup analyses were performed to estimate the lifetime, 12‐month, and point prevalence (Figure 5). The estimated lifetime prevalence was 90% (95% CI, 76%–96%; I 2 , 91%), based on data from six studies with a combined sample size of 626 3,4,10,12,13,15 . The 12‐month prevalence, reported in only one study with a sample size of 67 surgeons, was 63% (95% CI, 51%–73%) 11 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations